The term of Qur’ānic origin Amr Allāh (‘God’s Order’) and Islamic transcendental linguocentrism around the twelfth century - Peña, Salvador (Anaquel de Estudios Árabes, 2011)
Appart from its frequent occurrences throughout the Qur’ānic text, the term Amr Allāh, or al-Amr when referred to the godhead, has been approached from an essentialist paradigm which tends to regard it as a symbol or a holy entity by itself. So considered, the term Amr Allāh has been at the very core of what may be called ‘transcendental linguocentrism’ in several trends of Islamic thinking, around sixth Century AH / twelfth century CE. The term and its implications are explored in a wide range of discourses, in particular (1) the Almohad discourse, (2) the Aarite conceptions of the uncreatedness of the Qur’ān as well as the ethical principles, and (3) Islamic cosmologies; taking into account parallel notions in different religious of philosophical traditions from outside the Islamic realm.